PERANCANGAN APLIKASI PENGGAJIAN KARYAWAN BERBASIS ANDROID DAN DART FLUTTER PADA PT ANDALAN K3 MENGGUNAKAN MODEL WATERFALL - Wiguna, Nafis Surya; Nanang, Nanang (Jurnal Multidisipliner Bharasumba, 2024)
In the era of digital transformation, the use of mobile technology, especially Android, has become common and has had a significant impact on various aspects of life, including the business world. By involving many employees who use Android devices as their primary tool, the opportunity to increase affordability and convenience through Android-based payroll applications is enormous. The Waterfall method was chosen as a systematic approach in designing this application. The steps from system requirements, analysis, design, coding, testing/verification, to maintenance are carried out sequentially and structured. This study entitled "Design Of An Android And Dart Flutter Based Employee Payroll Application At Pt Andalan K3 Using The Waterfall Model" aims to speed up the payroll process, reduce the risk of errors, and increase employee satisfaction through a better experience in accessing their salary information. Thus, it can be proven that the design of an Android-based payroll application at PT Andalan K3 provides easy and fast access for employees to view salary information, submit changes to personal data, and receive notifications regarding salaries and allowances.